THE FUTURE OF “LANDS” IN ROMANIA - POMPEI COCEAN (Revue Roumaine de Géographie)
“Land”-type spatial entities are extremely well-outlined in Romania through a complex of favourable factors (natural, historical, economic, social, and cultural). They form both well-articulated territorial systems and typical mental spaces. Due to these structural and functional attributes, “lands” fall into the category of programme regions endowed with systems features of great authenticity and viability. The present paper analyses the prospects of future evolutions in terms of their characteristic territorial cohesion, national brand attributes and economic and social resilience through conversion from traditional agriculture and wood-processing to rural tourism.